Necropolitics and criminal interviews in Brazil: An analysis of the legacy of torture and the Mendéz Principles - Dos Santos de Almeida, Mariana (Revista de Estudios de la Justicia, 2024)
Brazil has the third-largest prison population in the world, yet it continues to face a high crime rate in society. Despite frequent arrests in flagrante delicto, the justice and security systems struggle to combat organized crime. The prevalence of torture and abusive practices during investigations and criminal interviews—practices still regarded by some as an effective means of crime control—undermines justice, perpetuates wrongful convictions, and disproportionately affects Black victims, reflecting entrenched systemic necropolitics and institutional racism. Through a qualitative analysis of legal frameworks, human rights reports, jurisprudence, and cases of police violence, the study identifies structural challenges in addressing these abuses. The article advocates for the adoption of the Méndez Principles for ethical and effective criminal interviews by implementing structural reforms. While acknowledging its limitations, the study seeks to contribute to bridging the gap between international human rights standards and Brazil’s unique socio-political context. It is aimed to support the alignment of Brazil’s security and justice practices with democratic and human rights principles, thereby fortifying the Constitutional State.